THE IMPORTANCE OF CUSTOMER SATISFACTION AND CUSTOMER COMPLAINT TOWARDS A BETTER QUALITY SERVICE USING SIX SIGMA: AN ACADEMIC PERSPECTIVE (Sains Humanika, 2010)
The purpose of this study is to evaluate the service quality that Multimedia University library (MMU) Malacca provides to its customers, by measuring the customersâ€™ level of satisfaction and judgment on the importance and effectiveness of customer complaints management system implemented by MMU library. A total of 253 samples were gathered from 300 questionnaires distributed among regular users of MMU library. A questionnaire was designed and used as the data gathering instrument based on the SERVQUAL model which consists of five dimensions (tangibles, reliability, responsiveness, assurance and empathy). The modification of SERVQUAL questionnaires examines the gap between perceived value and expectations of customersâ€™ towards the services provided. The concept of â€œgap analysisâ€ was applied to indicate actual satisfaction level of customers towards the selected dimensions in the SERVQUAL model. Closed ended questions were selected for both areas, satisfaction and complaint management. Based on a five point Likert scale, respondents are required to rate their satisfaction level according to their experienced with MMU Library. The study found that the dimensions of responsiveness and empathy were at the lowest satisfaction level among MMU students. Recommendations and suggestions are presented in this study to improve the service quality of MMU (Malacca) Library by using the six sigma model. Six sigma is a way to measure the probability that companies can manufacture or produce any given unit of a product (or service) with zero defects. In statistics, sigma (Ïƒ) denotes the standard deviation of a set of data. It provides a measure of variability which indicates how all values in a statistical distribution vary from the mean (average) value. Six sigma is the rating that signifies â€œbest in class,â€ with only 3.4 defects per million units or operations.
Keywords: Quality service; customer satisfaction; SERVQUAL; complaint management; six sigma